Breast Cancer: Correlation Between Vitamin D, Mammographic Density And Breast Cancer Risk In Pakistan. - Bushra Wasim (ziauddin University, 2024)
Pakistan comes under the category of countries with significant cancer load and surprisingly rising trends of risk factors. Amongst all the cancers, Breast cancer takes the lead. It has been reported to be accountable for one third of the cancers in the females....